PP04 Psychosocial mediators of change in physical activity in the Welsh National Exercise Referral Scheme: secondary analysis of a randomised controlled trial. (2nd September 2014) - Littlecott, HJ; Moore, GF; Moore, L; Murphy, S
Abstract : Background: Exercise referral schemes (ERS), involving health professional referral to a community exercise facility, are common in the UK. While an increasing number of randomised controlled trials report on the impacts of ERS on physical activity, few have investigated the mechanisms through which increases in physical activity are produced. This study examines whether a National ERS in Wales led to improved autonomous motivation, self-efficacy and social support, and whether changes in physical activity were mediated by these psychosocial processes. Methods: The study was a pragmatic randomised controlled trial across 12 Local Health Boards in Wales. Patients were recruited from 12 local health boards across Wales using opportunistic referral by a range of health professionals. Questionnaires measured demographic data and physical activity at baseline. Participants (N=2160) with Coronary Heart Disease (CHD) risk factors or anxiety/depression were referred by health professionals and randomly assigned to control or intervention. At six months psychological process measures were collected by questionnaire. At 12 months physical activity was assessed by Seven Day Physical Activity Recall telephone interview. Regressions tested intervention effects on psychosocial variables and physical activity before and after adjusting for mediators and socio-demographic patterning. The main trial indicated effects on physical activity only for patients referred for CHD risk, mediational analyses were limited to this subsample. Results: Significant intervention effects were found for autonomous motivation and social support for exercise at 6 months. The data supports partial mediation of the intervention effect by autonomous motivation. Analysis of moderators showed significant improvements in relative autonomy in all subgroups. The greatest improvements in autonomous motivation were observed among patients who were least active at baseline. Conclusion: The present study offered key insights into psychosocial processes of change in an exercise referral scheme, with effects on physical activity partially mediated by autonomous motivation. The nature of the study as a pragmatic policy trial means that the findings are directly reflective of real world practice. Findings support the use of self-determination theory as a framework for ERS. Further research is required to explain socio-demographic patterning in responses to ERS, with changes in motivation occurring among all sub-groups of participants, though not always leading to higher adherence or behavioural change. This highlights the importance of socio-ecological approaches to developing and evaluating behaviour change interventions, which consider factors beyond the individual, including conditions in which improved motivation does or does not produce behavioural change.